Effect of peppermint oil (mentha piperita) supplementation in quail diets on egg production and some egg quality characteristics, oxidative stress parameters and lipid profile - Şevket EVCİ; Miyase ÇINAR; Erva ESER; Kanber KARA; Ali ŞENOL (Kafkas Universitesi Veteriner Fakültesi Dergisi)
This study investigated the effects of peppermint oil supplementation in the diet of Japanese quail on egg production, quality characteristics, oxidative stress parameters, and lipid profile. A total of 90 female quail were divided into three groups: a control group, a low-dose group receiving 150 mg/kg peppermint oil, and a high-dose group receiving 300 mg/kg supplementation. The study lasted for 8 weeks during which external and internal egg quality characteristics, biochemical and lipid profile analyses were performed. The results indicated that low doses of peppermint oil had beneficial effects on eggshell weight and quality. In contrast, high doses of peppermint oil had negative effects on egg internal quality unit (IQU) and increased egg pH. A significant increase in omega-3 fatty acids, especially eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), was observed in the high-dose peppermint oil group, indicating an improvement in the lipid profile. While the low dose of peppermint oil improved certain egg quality parameters, the high dose had negative effects, highlighting the importance of determining the correct dosage of supplementation. Overall, the study shows that peppermint oil, when used at the appropriate dose, can improve both egg quality and lipid profiles, potentially offering health benefits by increasing beneficial fatty acids such as omega-3 in quail eggs.